(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2024)
The origin and development of Bioethics have gone hand in hand with bioethics committees, so it can be said that our Bioethics is a collegial one, not in terms of its foundation, but in terms of its working methodology. This paper analyzes the role that committees will play in the future, concluding that the new way of regulating uncertainty will grant them, along with the Courts of Justice, an even more important and necessary position in the future.